Hispanic Patients Undergoing Spinal Fusion for Neuromuscular Scoliosis Sustain Health Inequalities - Armando S. Martinez; David Momtaz; Travis Kotzur; Alexandra McLennan; Abdullah Ghali; Farhan Ahmad; Ebubechi Adindu; Alan C. Santiago-Rodriquez; Ali Seifi; Brian Smith (Spine Surgery and Related Research)
Introduction: Pre- and postoperative optimization remains a complex process impacted by various demographic factors. Our study aims to identify and describe those demographic factors associated with poor outcomes after spinal fusion with instrumentation in neuromuscular scoliosis to reduce health disparities and improve postoperative outcomes. Methods: A retrospective analysis was conducted using Healthcare Cost and Utilization Project data from 2016 to 2020, encompassing a random sample of 20% of procedures in the United States. Data included demographic and hospital variables, including days from admission to the procedure, length of stay, recovery time, total charge, discharge disposition, and mortality rates. In addition to ANOVA, Chi-Squares, and t-tests, multiple-linear and multiple-logistic regression models were designed and run to generate adjusted odds ratios. Results: Compared to non-Hispanic patients (N=1829), Hispanic patients (N=431) had spinal fusion with instrumentation at younger ages (12.9 vs. 14.1 years old, p=0.011) and had significantly different household incomes with less representation in the 75th to 100th percentile (16.8% vs. 26.5%, p<0.001). Additionally, Hispanic patients were more likely to be Medicaid users (67.2% vs. 46.0%, p<0.001). Hispanic patients undergoing spinal fusion with instrumentation had longer lengths of stay (LOS) (10.0 vs. 7.6 days, p<0.001), longer periods from admission to surgery (wait time) (1.6 vs. 1.0 days, p=0.046), and longer recovery times (8.5 vs. 6.7 days, p<0.001). Conclusions: Hispanic patients with NMS often have longer lengths of stay, longer periods between admission and surgery, and longer recovery times than non-Hispanic patients. This difference in hospital courses and surgical timing could be an effect of disparities in healthcare access and socioeconomic standing. Further efforts are required to both understand and reduce barriers to healthcare access in the Hispanic patient population undergoing spinal fusion with instrumentation.